(untitled) (Research, Society and Development, 2024)
Glucocorticoids are medications of wide medical use, notably due to their known anti-inflammatory effects. Furthermore, fluctuations in glycemic indexes stand out as risk factors for clinical and surgical complications, mortality and increased hospital stay. The study consists of an integrative and descriptive literature review, through the PUBMED platform with the following keywords: “Hyperglycemia”, “Glucocorticoid” and “Induce”, in the last 12 years and aims to gather and unify information regarding the understanding and clinical and therapeutic management of hyperglycemia induced by the use of corticosteroids and corticogenic diabetes. The fluctuation in glycemic indexes with the use of corticosteroid therapy is an imbalance between the increase in insulin resistance and the inhibition of insulin production and secretion at the pancreatic cellular level. Screening for Diabetes Mellitus in patients on corticosteroid therapy is based on consensus in the literature with a plasma glucose level above 125 mg/dL, any capillary measurement above 200 mg/dL, HbA1c> 6.5% or oral tolerance test glucose above 200mg/dL after 2 hours. The main glycemic target is capillary blood glucose between 108-180 mg/dL and in cases of initiating therapeutic approaches for hospital management of glycemic fluctuations, the use of insulin therapy is chosen. Hyperglycemia induced by the use of corticosteroids is a topic that has been gaining prominence in the medical scenario, despite the lack of studies that uniformly protocol the approach to patients when this scenario is confirmed, with the aim of reducing the risks associated with hospitalization.